2001
DOI: 10.1039/b109535h
|View full text |Cite
|
Sign up to set email alerts
|

The d2/d3 alkyne redox pair [WF2(PhCCPh)Tp′]z (z = +1 or 0): missing links in a ‘redox family tree’

Abstract: The d2/d3 redox pair [WF2(PhC identical to CPh)Tp']z [z = +1 or 0, Tp' = hydrotris(3,5-dimethylpyrazolyl)borate] is the missing link in a 'redox family tree' relating the d6 tricarbonyls [M(CO)3L]- to the d2 trihalides [MX3L] (M = Mo or W, L = Cp or Tp') by a series of stepwise reactions involving sequential one-electron oxidation followed by ligand substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Indeed, the optical isomers of [WI(CO)(g-MeC≡CMe)Tp ] have been separated. 10 In addition, the 13 C chemical shifts for the metal-bound alkyne carbons (two for each complex), at 194-219 ppm, are consistent with four-electron alkynes. 9 Each of the but-2-yne complexes [MX(CO)(g-MeC≡CMe)Tp ] (1-5 and 10-14) shows two sharp singlets in both the 1 H NMR (in the range 2.71-3.39 ppm) and 13 C{ 1 H} NMR spectra (between 18 and 23 ppm) for the alkyne methyl substituents, suggesting that no alkyne rotation occurs at ambient temperature; variable-temperature NMR spectroscopic studies also showed a high barrier to alkyne rotation for [WI(CO)(g-PhC≡CH)Tp ]…”
Section: Nmr Spectroscopymentioning
confidence: 84%
See 3 more Smart Citations
“…Indeed, the optical isomers of [WI(CO)(g-MeC≡CMe)Tp ] have been separated. 10 In addition, the 13 C chemical shifts for the metal-bound alkyne carbons (two for each complex), at 194-219 ppm, are consistent with four-electron alkynes. 9 Each of the but-2-yne complexes [MX(CO)(g-MeC≡CMe)Tp ] (1-5 and 10-14) shows two sharp singlets in both the 1 H NMR (in the range 2.71-3.39 ppm) and 13 C{ 1 H} NMR spectra (between 18 and 23 ppm) for the alkyne methyl substituents, suggesting that no alkyne rotation occurs at ambient temperature; variable-temperature NMR spectroscopic studies also showed a high barrier to alkyne rotation for [WI(CO)(g-PhC≡CH)Tp ]…”
Section: Nmr Spectroscopymentioning
confidence: 84%
“…The IR spectra were recorded on a Nicolet 5ZDX FT spectrometer or a Perkin Elmer Spectrum One FT-IR spectrometer fitted with a Perkin Elmer ZnSe Universal ATR sampling accessory. Proton, 13 C{ 1 H} and 19 F NMR spectra were recorded on JEOL GX270, Eclipse 300 or GX400 spectrometers with SiMe 4 or CCl 3 F (for 19 F) as internal standards. All spectrometers operated in the Fourier transform mode, with field stability maintained by an external lock system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insight into the structure and bonding of metal alkyne complexes has also been gained by systematic study of their redox properties. In particular, the ramifications of changes in both formal d-electron count and the number of electrons donated by the alkyne ligands across a series of complexes have been elegantly probed. These studies demonstrate that alkyne ligands are extremely flexible in the bonding modes that they can adopt within the coordination sphere of metals: a property that may enhance their reactivity . As well as providing insight into the electronic structure of metal alkyne complexes, one-electron-transfer reactions may also initiate some interesting intramolecular ligand couplings.…”
Section: Introductionmentioning
confidence: 99%